Perlindungan Hukum terhadap Pemenang Lelang Hak Tanggungan dalam Persepektif Peraturan Perundang Undangan Indonesia - Arikatul Faizah; Zaini Zaini; Mohammad Nurul Huda (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2026)
This study aims to analyze legal protection for auction winners of mortgage rights within the framework of Indonesian laws and regulations. The auction of mortgage rights serves as a mechanism for executing secured collateral with binding legal force; however, in practice, it often raises legal issues, particularly concerning legal certainty and protection for auction winners. This research employs a normative juridical method using statutory and conceptual approaches. The findings indicate that legal protection for auction winners has been regulated under various laws, including the Mortgage Law, auction regulations, and provisions governing collateral execution. Nevertheless, challenges remain in its implementation, such as lawsuits filed by debtors or third parties that hinder the transfer and control of auctioned objects. This condition reflects a discrepancy between legal norms and their practical application. Therefore, strengthening regulations and ensuring consistency among law enforcement authorities are necessary to guarantee legal certainty and protection for auction winners. This study is expected to contribute to the development of secured transactions law and the improvement of auction practices in Indonesia.